Regions in Information Society – a Hungarian Case-Study - Csatári, Bálint; Kanalas, Imre; Nagy, Gábor; Szarvák, Tibor (Discussion Papers, 2012)
In our paper we are going to provide an analysis on the existing special interactions between the spatial features information technology and the evolution of society. We are also going to investigate the special role of regions, the ‘spatial locations’ of the development of information society. The answer for the first issue is relatively easy. It covers only the review of the spatial features of the installation and evolution of information infrastructure and technology of the near past. This problem arise a new interesting question: whether the spatial diffusion of IT development follows a similar pattern to that of traditional linear infrastructure (telephone, public road) or implies new forces of spatial development? To answer the second issue is far more complicated. Regions within the ‘virtual space’ of information society - several so-called ‘intelligent region’ projects are running within West European states - may be interpreted in two ways. Partly in concrete, partly in abstract forms. The results of scientific or public interpretations on regions and other spatial units (counties, micro-regions) - they are available on different information channels and networks - may only be evaluated in an indirect way. However, the extremely high visitors’ traffic at the websites of regional development verifies that there is a growing general interest for regional science information. This indicates that the development of information society and infrastructure has some spatial features and regional aspects that deserve special attention.